Transacting with Digital Money on View of Islamic Law - Abubakar Muhammad; Muhammad Hamma’Adama Ahmad (Demak Universal Journal of Islam and Sharia, 2023)
This research aims to show the dealing with digital money from the perspective of the Islamic. The researcher in this section has mentioned the talk about dealing in digital electronic money from the perspective of the Islamic. He mentioned the definition and the concept of money, and its history and types. He singled out the talk about digital electronic money in terms of its concept and history, and between the rule of dealing with it from the sayings of contemporary scientists that clarify the meaning of what is intended, and the position of the researcher in it, and the problem is currently that many people do not know digital electronic money as well as the rule of dealing with it, it has become necessary to find scientific research that shows and shows the legal ruling in dealing with it. This study is based on combining approaches based on the nature and style of research, and highlighted The methods used and required by the study are the inductive method, the texts, and the analytical method, which analyzes these texts, and explains some strange words and terms if necessary. Then the researcher used the field study to collect data from books and studies, and then analyze these texts and studies from the sayings of contemporary scholars in electronic and digital money, such as the fatwas of the General Authority of Islamic Affairs and Endowments in Dubai, the fatwas of the Palestinian Dar Al-Iftah, the fatwas of the Egyptian Dar Al-Iftah, and others and others. Then the position of the researcher and weighting. This section contained an introduction and four sections, and in conclusion, the researcher shed light on the most prominent section of the most important results reached by suggestions and recommendations, then references sources and indexes. يهدف هذا البحث إلى بيان التعامل بالنقود الرقمية في منظور الإسلامي .وقد أورد الباحث في هذا المبحث الكلام حول التعامل في النقود الإلكترونية الرقمية في منظور الإسلامي. أورد التعريف ومفهوم النقود، وتاريخه وأنواعه وخص الكلام حول نقود الإلكترونية الرقمية من حيث مفهومه وتاريخه ، وبين حكم التعامل بها من وأقوال العلماء المعاصرين التي توضح معنى المراد، وموقف الباحث فيها، والمشكلة حاليا أن كثيرا من الناس لا يعرفون نقود الإلكترونية الرقمية فضلا عن حكم التعامل بها، أصبح من الضروري أن يوجد بحثا علميا يظهر ويبين حكم الشرعي في التعامل بها، وتقوم هذه الدراسة على الجمع بين مناهج بناء على طبيعة البحث وأسلوبه، وأبرز المناهج المستعملة والتي تقتضيها الدراسة هما المنهج الاستقرائي النصوص، والمنهج التحليل ، التي تقوم بتحليل هذه النصوص، وشرح بعض الكلمات الغريبة والمصطلحات،إذا دعت إلى ذلك حاجة. ثم أن الباحث استعمل الدراسة الميدانية، لجمع البيانات من الكتب والدراسات،ثم تحليل هذه النصوص والدراسات من أقوال العلماء المعاصرين في النقود الإلكترونية والرقمية، مثل فتاوى الهيئة العامة للشؤون الإسلامية والأوقاف في دبي، وفتاوى دار الإفتاح الفلسطينية، وفتاوى دار الإفتاح المصرية ، وغيرهم وغيرهم. ثم موقف الباحث والترجيح. فقد احتوى هذا المبحث على مقدمة وأربعة مباحث، وفي الختام، فقد القى الباحث ضوءا على أبرز ما في المبحث من أهم النتائج التي توصل اليها من اقتراحات وتوصيات، ثم المراجع والمصادر والفهارس.